α6β4 integrin genetic variations (A380T and R1281W) and breast cancer risk in an Argentinian population - Acosta, Karina Beatriz (2016)
The α6β4 integrin is composed of the α6 and β4 subunits that are encoded by the ITGα6 and the ITGβ4 genes, respectively. The α6β4 main function is to intervene in lamination and epithelia integrity maintenance by cell-matrix interactions. This integrin appears to have importance in breast cancer malignancy, as well as other epithelial carcinomas. The aim of this work was to investigate the potential role of ITGα6 (A380T) and ITGβ4 (R1281W) genetic variations in breast cancer susceptibility, in a female population from the northeast region of Argentina (Misiones). We performed a case-control study of 85 breast cancer patients and 113 cancer-free controls. Genotyping was performed by RFLP-PCR. For ITGα6 (A380T) single nucleotide polymorphism, a high frequency of heterozygous genotype GA in cases compared to controls was observed, achieving values of 48% and 49%, respectively. No association between the A380T SNP and breast cancer development was found (Odds Ratio = 0.92; 95% Confidence Interval = 0.52-1.63; p = 0.884). In conclusion, we did not find evidence of an association between A380T (ITGα6) and the risk of developing breast cancer. The results represent the first report of these genetic variations in breast cancer; therefore, they are an important contribution to the literature.